Domestic water security in the Arctic : a scoping review - Cassivi, Alexandra; Covey, Anna; Rodriguez, Manuel J.; Guilherme, Stéphanie (International Journal of Hygiene and Environmental Health, 2022)
Introduction: More than 50 million people living in the Arctic nations remain without access to safely managed drinking water services. Remote northern communities, where large numbers of Indigenous peoples live, are disproportionally affected. Recent research has documented water and health-related problems among Indigenous communities, including poor water quality and insufficient quantities of water. Objective: The objective of this scoping review is to examine the extent of available water security evidence as well as identify research gaps and intervention priorities to improve access to domestic water in the Arctic and Subarctic regions of the eight Arctic nations (Canada, the Kingdom of Denmark (Greenland), Finland, Iceland, Norway, Sweden, Russia, and the United States (Alaska)). Methods: An extensive literature review was conducted to retrieve relevant documentation. Arctic & Antarctic Regions, Compendex, Geobase, Georef, MEDLINE and Web of Science databases were searched to identify records for inclusion. The initial searches yielded a total of 1356 records. Two independent reviewers systematically screened identified records using selection criteria. Descriptive analyses were used to summarize evidence of included studies. Results: A total of 55 studies, mostly conducted in Canada and the United States, were included and classified by four predetermined major dimensions: 1) Water accessibility and availability; 2) Water quality assessment; 3) Water supply and health; 4) Preferences and risk perceptions. Conclusions: This scoping review used a global approach to provide researchers and stakeholders with a summary of the evidence available regarding water security and domestic access in the Arctic. Culturally appropriate health-based interventions are necessary to ensure inclusive water services and achieve the Sustainable Development Goals (SDG) targets for universal access to water.